Impact of Quality Management Practices on Manufacturing Performance - Mohd Akhir; Rosman Iteng; Mohd Kamarul Irwan Abdul Rahim (International Journal of Supply Chain Management, 2017)
Abstract Quality management practices are important agenda to be implemented by the manufacturing for their survival. Different sector of industries has different element of quality management practices, this study it concern varying constructs of quality practices are required to be implemented according to their field. This study also is to examine the relationship of quality management practices and manufacturing performance in the Malaysian automotive industry. For the purpose of study, a questionnaire was developed and distributed among the automotive vendors based on sample random sampling. Framework of conceptual model using PLS-SEM analysis. This proposal framework model in this study is to investigate the causal relationship between the variables of quality management practices on manufacturing performance.